Analisis Peran Weton Dalam Kegagalan Pernikahan Menurut ‘Urf Dan Maqasid Al-Shari’ah - Mahfudz Alfi Salam; Rudy Catur Rohman Kusmayadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The weton tradition in Javanese society is part of a long-standing cultural system used to assess the compatibility of marriage partners. Though rooted in ancestral heritage, this practice continues to significantly influence decisions surrounding marriage and divorce in the modern era. This study aims to analyze the influence of weton on marital continuity and examine how Islamic law positions this practice within the framework of ʿurf and maqāṣid al-sharīʿah. Employing a qualitative-descriptive approach, data were collected through interviews, observation, and documentation in communities across East Java. The findings indicate that weton is often a primary consideration in marriage decisions and plays a role in household conflicts and even divorce, despite actual causes stemming from poor communication, familial pressure, or economic stress. From the Islamic legal perspective, weton may be accepted as ʿurf ṣaḥīḥ (valid custom) as long as it does not violate the principle of tawḥīd or cause harm. However, when weton is believed to be absolute and used to annul a legitimate marriage, it becomes ʿurf fāsid (invalid custom). This study recommends an educational and integrative approach to interpreting weton so that local traditions may be preserved without compromising Islamic principles